Investigation of CO2 storage and EOR of alternating N2 and CO2 injection using experiments and numerical simulation. (15th May 2023) - Li, Zongfa; Su, Yuliang; Shen, Fuxiao; Huang, Lijuan; Ren, Shaoran; Hao, Yongmao; Wang, Wendong; Meng, Yang; Fan, Yang
Highlights: Feasibility investigation of N2 alternating CO2 injection for improving CO2 storage and oil production. Analysis of mobility adjustment by N2 slug during continuous CO2 injection. Comparison of gas channeling phenomenon, gas swept area, EOR, and CO2 storage of different gas injection methods at a field scale. Recommendation of potential oil reservoirs suitable for NAC technology. Abstract: The feasibility of N2 alternating CO2 injection was investigated for improving CO2 storage and oil production. Schemes of continuous CO2 injection and N2 alternating CO2 injection were evaluated using laboratory experiments and numerical simulation. According to the core flooding experiments, the CO2 storage factor and enhanced oil recovery of N2 alternating CO2 flooding were 2.1% and 7.1% lower than continuous CO2 injection. The larger the N2 slug volume in N2 alternating CO2 injection, the lower the EOR and CO2 storage factor due to the reduction of CO2 concentration in the gas phase and CO2 solubility in oil and water. However, the N2 slugs in N2 alternating CO2 injection significantly reduced mobility differences between different flowing zones, and thus can increase the gas swept area in an oil reservoir. The gas swept area of the oil reservoir under N2 alternating CO2 injection mode is 1.78 times that of continuous CO2 injection, resulting in a 44% higher cumulative oil production. Besides, the scheme of N2 alternating CO2 injection was optimized and resulted in 19.6% more CO2 storage than continuous CO2 flooding at a field scale. This study provides valuable experimental and theoretical support for improving CO2 storage and oil production in an oil reservoir.